Intake and digestibility of four rations with different fiber levels in alpacas (Vicugna pacos) - Obregón Cruz, Ana B. (2024)
The aim of this study was to evaluated the impact of different fibre levels in alpaca diet on voluntary feed intake and apparent digestibility, and to estimate the digestibility of organic matter (OMD) from the content of crude protein (CP) in feces. The study was carried out with twelve alpacas (36.7 ± 6.4 kg body weight- BW), which were offered 4 treatments with different neutral detergent fiber content (NDF. T1: 40.3%; T2: 62%; T3: 68%; T4: 72%) under a switch back design. Absolute daily dry matter intake (DMI) was higher for T1 (678 g/d) than T4 (312 g/d) (p ≥ 005). NDF intake was similar between treatments when related to BW or MW (on average 1% BW and 22 g/kg MW. p ≥ 0.05). Water intake (L/kg DMI) was higher in T1 compared to the other treatments, with values ranging from 2.9 L/kg DMI(T1) to 2.8 L/kg DMI(T4), respectively (p ≤ 0.05). Digestibility of dry matter, organic matter and CP was higher in T1 than in the other treatments, with average values ranging from 72% for T1 to 32% for T4 (p ≤ 0.05). NDF digestibility was similar among treatments (p ≥ 0.05). The regression equation generated to predict OMD (y) was as follows: y = 0.360 + 0.08294*fecal CP (g/kg OM). Further studies will indicate whether faecal nitrogen can be used to estimate digestibility and hence diet quality in South American camelids.